2019
DOI: 10.1177/2284240319876574
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of economic evaluations in non-insulin antidiabetic treatments for patients with type 2 diabetes mellitus

Abstract: The approval of new non-insulin treatments has broadened the therapeutic arsenal, but it has also increased the complexity of choice for the treatment of type 2 diabetes mellitus (DM2). The objective of this study was to systematically review the literature on economic evaluations associated with non-insulin antidiabetic drugs (NIADs) for DM2. We searched in Medline, IBECS, Doyma and SciELO databases for full economic evaluations of NIADs in adults with DM2 applied after the failure of the first line of pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 70 publications
(151 reference statements)
0
7
0
Order By: Relevance
“…Similarly, add-on therapy of GLP1 receptor agonists to metformin was found to be cost-effective compared to insulin or DPP-4i therapy [55,58]. In addition, diabetes model-based simulations showed that GLP1 receptor agonists might be cost-effective in patients with or at high cardiovascular risk compared to the standard care [59,60].…”
Section: Cost Of Antidiabetic Medications and Cost-effectiveness-anal...mentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly, add-on therapy of GLP1 receptor agonists to metformin was found to be cost-effective compared to insulin or DPP-4i therapy [55,58]. In addition, diabetes model-based simulations showed that GLP1 receptor agonists might be cost-effective in patients with or at high cardiovascular risk compared to the standard care [59,60].…”
Section: Cost Of Antidiabetic Medications and Cost-effectiveness-anal...mentioning
confidence: 98%
“…As first-line agents, SGLT-2 inhibitors and GLP-1 receptor agonists would improve type 2 diabetes outcomes, but they are probably not cost-effective compared to metformin due to their high medication costs [54]. However, several studies showed that SGLT-2 inhibitors and GLP-1 receptor agonists as an add-on therapy to metformin are cost-effective and maybe cost-saving compared to other antidiabetic drugs [55]. In particular, in combination with metformin, SGLT-2 inhibitor treatment is cost-effective or even costsaving compared to DPP-4i, sulfonylurea, or glitazone medication [55].…”
Section: Cost Of Antidiabetic Medications and Cost-effectiveness-anal...mentioning
confidence: 99%
See 1 more Smart Citation
“…Non-adherence to treatment is due to forgetting the daily injections, especially when more doses are needed, and the short duration of the disease [39]. (9) The administration of various new antidiabetic therapies (DPP4, SGLT2 inhibitors) shall be conducted with caution and not on a large scale, due to the short-and long-term effectiveness uncertainty and due to possibly severe side effects [40].…”
Section: Cluster 4-medication Therapy Algorithmmentioning
confidence: 99%
“…Existing guidelines and evidence recommend metformin as first-line treatment, sulfonylurea as second-line treatment (or first-line treatment if metformin is contraindicated) and insulin as third-line treatment [ 3 5 ]. Increasing evidence have suggested that anti-diabetic medications (ADMs) reduce the incidence of long-term complications, hospital admission, and mortality among patients with diabetes [ 6 ].…”
Section: Introductionmentioning
confidence: 99%